Sources, quality and transfers of organic matter in a highly-stratified sub-Arctic coastal system (Saint-Pierre-et-Miquelon, NW Atlantic). (January 2021) - Bridier, Guillaume; Meziane, Tarik; Grall, Jacques; Chauvaud, Laurent; Donnet, Sébastien; Lazure, Pascal; Olivier, Frédéric
Highlights: Enhanced stratification negatively impacts POM quality and availability. Increased stratification reduces pelagic-benthic coupling. SOM compartment is more independent of changes occurring in the water column. Benthic primary production may partly offset decreases in POM quality/availability. Abstract: In response to ongoing global climate change, marine ecosystems in the northwest Atlantic are experiencing one of the most drastic increases in sea surface temperatures in the world. This warming can increase water column stratification and decrease surface nutrient concentrations, in turn impacting primary productivity and phytoplankton assemblages. However, the exact impacts of these changes on sources and quality of organic matter as well as its transfers to the benthic compartment remain uncertain. This survey characterized organic matter sources and quality within a highly-stratified sub-Arctic coastal system (Saint-Pierre and Miquelon) and described its transfer towards a biomass-dominant primary consumer, the sand dollar Echinarachnius parma . This study analyzed fatty acid and stable isotope (δ 13 C and δ 15 N) composition of surface and bottom Particulate Organic Matter (s-POM and b-POM, respectively), Sedimentary Organic Matter (SOM) and sand dollar tissue along a near shore to offshore gradient during two contrasting seasons associated either with sharp or weak water column stratification (i.e. High vs Low Stratification Periods). Results revealed high relative abundances of polyunsaturated fatty acids (notably macro- and microalgae markers) in POM during the Low Stratification Period while the High Stratification Period was characterized by elevated relative abundance of saturated fatty acids indicating a higher organic matter degradation state. In addition, strong seasonal differences were also observed in food availability with four-fold higher concentrations in total suspended solids during Low vs High Stratification Periods. These results suggested thus multiple negative effects of stratification on pelagic-benthic coupling and POM quality. Lower nutrient repletion of surface waters during period of sharp stratification diminishes pelagic-benthic coupling by reducing food availability, POM quality and vertical transfer of organic matter. By contrast, the sediment-based diet of E. parma showed a low spatiotemporal variability reflecting the homogenous composition of the SOM. This study suggests that intensified water column stratification due to increasing sea surface temperatures may modify the pelagic-benthic coupling and future quality and composition of POM pools.